A Model of Shallow Viscoelastic Relaxation for Seismically Induced Tension Cracks in the Chile‐Peru Forearc. Issue 19 (15th October 2019) - Luo, H.; Wang, K.; Sone, H.; He, J.
Abstract: Tension cracks were generated by past megathrust earthquakes along the coastal forearc of Chile‐Peru. To explain why elastic rebound in an offshore earthquake can cause widespread permanent deformation onshore, we propose a model in which the near‐surface material exhibits viscoelastic behavior, analogous to laboratory‐observed behavior of petroleum reservoir rocks. Because of near‐surface relaxation, interseismic deformation builds up stress only in the deeper crust. Elastic rebound of the deeper crust during an earthquake induces near‐surface tension to generate cracks. We numerically demonstrate the proposed mechanism using hypothetical and real megathrust earthquakes. The location of the zone of peak tension, assumed to be responsible for the crack generation, is controlled by downdip rupture termination. A rupture farther downdip or terminating more gradually causes the zone of peak tension to be farther landward and broader. The tension cracks thus may contain important information on megathrust rupture dynamics. Plain Language Summary: Earthquakes are the operation of elastic rebound. Tension cracks induced by megathrust earthquakes observed in Chile‐Peru therefore require special explanation. In this work, we propose a testable model for these cracks. We propose that the cemented soil and the highly fractured shallow bedrock in this area exhibit a viscoelastic behavior analogous to petroleum reservoir rocks. When the megathrust is locked in preparation for the next earthquake, the deeper crust is elastically shortened like a spring, but the shallow material deforms in a viscous fashion and do not store energy. During the megathrust earthquake, elastic rebound of the deeper crust induces tension in the shallow material, causing it to crack. If we assume that the observed crack distribution is controlled by the peak tension during the earthquake, it can be used to constrain how the megathrust rupture terminates in the deep end, which helps to understand the physics of earthquakes. Key Points: Viscoelastic relaxation of near‐surface material allows permanent interseismic shortening contemporaneous with deeper elastic deformation Elastic rebound of deeper crust in earthquakes induces tension in the relaxed shallow material, explaining cracks in Chile‐Peru forearc Crack distribution, assumed to be controlled by peak coseismic tension, contains important information on megathrust rupture termination